Dimensions of interoception predict premonitory urges and tic severity in Tourette syndrome. (January 2019) - Rae, Charlotte L; Larsson, Dennis E O; Garfinkel, Sarah N; Critchley, Hugo D
Highlights: Interoceptive accuracy is numerically lower in TS than controls but not significant. Discrepancy between interoceptive accuracy and sensibility is elevated in TS. Interoceptive sensibility predicts severity of premonitory sensations and tics. Abstract: Interoceptive processes in Tourette syndrome may foster the premonitory urges that commonly precede tics. Twenty-one adults with TS and 22 controls completed heartbeat tracking and discrimination tasks. Three dimensions of interoception were examined: objective accuracy, metacognitive awareness, and subjective (self-report) sensibility. Trait interoceptive prediction error was calculated as the discrepancy between accuracy and sensibility. Participants with TS had numerically lower interoceptive accuracy on the heartbeat tracking task, and increased self-reported interoceptive sensibility. While these group differences were not significant, the discrepancy between lower interoceptive accuracy and heightened sensibility, i.e. the trait interoceptive prediction error, was significantly greater in TS compared to controls. This suggests a heightened higher-order sensitivity to bodily sensations in TS, relative to a noisier perceptual representation of afferent bodily signals. Moreover, interoceptive sensibility predicted the severity of premonitory sensations and tics. This suggests interventions that work to align dimensions of interoceptive experience in TS hold therapeutic potential.